The Quest for the Origin of John's Gospel : a Source-Oriented Approach. - Brodie, Thomas L. (Oxford University Press, 1994)
This is a controversial thesis concerning the composition of the Gospel According to John. It argues that more must be discovered about the source of John's material, and that John himself was an individual, and not the mouthpiece of a putative "Johannine Community."